Literary studies a practical guide - Pugh, Tison; Johnson, Margaret E. (Routledge, 2014)
"Literary Studies: A Practical Guide provides a comprehensive foundation for the study of English, giving students the critical skills they need to best apply their knowledge"--Provided by publisher.